POLITICAL VIOLENCE AND SOCIAL CONFLICT DURING THE POPULAR UNITY GOVERNMENT. THE CASE OF VANGUARDIA ORGANIZADA DEL PUEBLO (VOP), 1970-1971 - Bonnassiolle Cortés, Marcelo Alejandro (2014)
This article examines the emergence and participation of revolutionary political group called la Vanguardia Organizada del Pueblo (VOP), an organization through a series of political operations tort, such as theft, expropriation and executions was formed as a critical actor whose activities and operations helped shape the destiny of the Popular Unity. VOP’s decision to continue the armed actions during that government and “execute” the former Minister Edmundo Perez Zujovic were instrumental in shaping and gestation of opposition political approach in their fight against the government of Salvador Allende, generating as Article shows the beginning of the end of the Popular Unity government.